2008
DOI: 10.1523/jneurosci.0973-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Mutant Huntingtin Aggregate Formation by Cdk5/p35 through the Effect on Microtubule Stability

Abstract: Huntington's disease (HD) is a polyglutamine [poly(Q)] disease with an expanded poly(Q) stretch in the N terminus of the huntingtin protein (htt).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Immunofluorescent Staining and Real-time ObservationCortical neurons were transfected with DsRed, p35-myc, and caFyn by a calcium phosphate method at 5 days in vitro (DIV), as described previously (30), and, 48 h after transfection, neurons were immunostained with anti-myc 4A6, followed by Alexa Fluor 488-conjugated secondary antibodies. Fluorescent images were captured with an LSM510 or LSM710 confocal microscope (Carl Zeiss, Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescent Staining and Real-time ObservationCortical neurons were transfected with DsRed, p35-myc, and caFyn by a calcium phosphate method at 5 days in vitro (DIV), as described previously (30), and, 48 h after transfection, neurons were immunostained with anti-myc 4A6, followed by Alexa Fluor 488-conjugated secondary antibodies. Fluorescent images were captured with an LSM510 or LSM710 confocal microscope (Carl Zeiss, Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…COS-7 cells (2 ϫ 10 5 per ml) were grown in DMEM (Sigma) containing 10% FBS and transfected with PolyFect reagent (Qiagen) (Kaminosono et al, 2008).…”
Section: Construction Of Expression Vectors For Tau Proteinsmentioning
confidence: 99%
“…5H). To exclude the possibility of detrimental effects from the overexpression of CDK5, we used a kinase-dead CDK5 (D144N) (44). We confirmed that CDK5 D144N interacted with UCH-L1 at a level comparable with that with CDK5 WT (supplemental Fig.…”
Section: Ectopic Expression Of Cdk5 Attenuates the Interaction Betweementioning
confidence: 57%